Cross-linked and hydrophobized hyaluronic acid-based controlled drug release systems - Csapó Edit; Szokolai Hajnalka; Juhász Ádám; Varga Norbert; Janovák László; Dékány Imre (2018)
This work demonstrates the preparation, structural characterization, and the kinetics of the drug release of hyaluronic acid (HyA)-based colloidal drug delivery systems which contain hydrophobic ketoprofen (KP) as model molecule. Because of the highly hydrophilic character of HyA the cross-linked derivatives at different cross-linking ratio have been synthesized. The hydrophobized variants of HyA have also been produced by modifying the polymer chains with cetyltrimethylammonium bromide (CTAB) at various HyA/CTAB ratios. Due to modifications the coherent structure of HyA changes into an incoherent colloidal system that were verified by rheological investigations. Nearly 70% of the encapsulated KP dissolve from the totally cross-linked HyA carrier but the release rate of KP is about 20% (after 8 h) from the CTAB-modified colloidal system at HyA monomer/CTAB 1: 0.8 mass ratio. It has been verified that the modified HyA may be a potential candidate for controlled drug release of hydrophobic KP molecules.